Projected Benefits Of The Free Nutritious Meals Program In Indonesia: A Comparative Analysis Based On Social Justice Theory And Human Capital - Pardomuan Robinson Sihombing (CV Pena Jaya Pers, 2025)
Background: Indonesia faces a paradoxical development phenomenon: intense and persistent economic growth, high child poverty rates, and stunting prevalence. The government initiated the Free Nutritious Meals Program (FNMP/ MBG) in response. Purpose: This study aims to analyze the projected multisectoral benefits of the MBG program. The method used is a theoretical qualitative literature review, framed by Human Capital Theory and Justice as Fairness Theory. Design/methodology/approach: A comparative analysis was conducted on school feeding programs in Brazil (PNAE), China (NNIP-RCES), and Japan (Kyūshoku). Findings: The results show that international programs have had a significant impact: PNAE in Brazil has empowered the local farming economy, NNIP-RCES in China has measurably improved academic achievement, and Kyūshoku in Japan has integrated nutrition with character education. Implication: These findings imply that MBG has the potential to be a strategic investment that not only improves nutrition but also enhances educational outcomes, stimulates the local economy, and functions as an instrument of fundamental social justice in Indonesia